2011
DOI: 10.1016/j.econedurev.2010.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Labour market mismatch among UK graduates: An analysis using REFLEX data

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
151
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(157 citation statements)
references
References 17 publications
4
151
0
2
Order By: Relevance
“…At the individual level, overeducated workers have been found to earn less than similarly educated workers whose jobs match their qualifications, presumably because a proportion of their investment in education is underutilized and unproductive (McGuinness and Sloane, 2011;Mavromaras et al , 2009;Bárcena-Martín et al, 2012) 1 .…”
Section: Determinants Of Regional Differences In Rates Of Overeducatimentioning
confidence: 99%
See 2 more Smart Citations
“…At the individual level, overeducated workers have been found to earn less than similarly educated workers whose jobs match their qualifications, presumably because a proportion of their investment in education is underutilized and unproductive (McGuinness and Sloane, 2011;Mavromaras et al , 2009;Bárcena-Martín et al, 2012) 1 .…”
Section: Determinants Of Regional Differences In Rates Of Overeducatimentioning
confidence: 99%
“…To date, research to identify the determinants of international differences in rates of overeducation has been limited. Thus, while we know much about the magnitude of overeducation effects on variables such as earnings, job satisfaction and career mobility (Battu, Belfield and Sloane (1999) and Dolton and Vignoles (2000), Peiró et al (2010), McGuinness (2003), McGuinness and Sloane (2011)), there is much less understanding of the structural factors that drive the overeducation phenomenon itself. With respect to the very limited work that does exist, Groot and van den Brink (2000), in a meta-analysis, found evidence of a relationship between overeducation and the rate of labour force growth.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies, some of which control for workers' fixed unobserved heterogeneity and/or field of education, also found that over-(under-)educated workers earn more (less) than their adequately educated peers. This implies, according to human capital theory, that over-(under-)education increases (decreases) workers' productivity (see e.g., Battu et al 1999;Dolton and Silles 2008;Duncan and Hoffman 1981;McGuinness and Sloane 2011;Sicherman 1991;Van der Meer 2006).…”
Section: Educational Mismatch and Firm Productivitymentioning
confidence: 99%
“…Other studies regarding the wage effects of educational mismatch also highlight that, in a given job with a specific level of required education, over-(under-) educated workers earn more (less) than those who have just the required education for the job (Battu et al, 1999, Dolton and Vignoles, 2000, Duncan and Hoffman, 1981, Groot, 1996, Groot and Maassen van den Brink, 2000, Sicherman, 1991, van der Meer, 2006. Although part of this premium (penalty) may be explained by workers' unobserved heterogeneity (Bauer, 2002, Chevalier, 2003, Dolton and Silles, 2008, Frenette, 2004, Lamo and Messina, 2010, McGuinness, 2003, McGuinness and Sloane, 2011, current evidence on the basis of human capital theory thus suggests that over-(under-) education increases (reduces) workers' productivity. 2 Another strand of the literature examines the impact of educational mismatch on job satisfaction and other correlates of workers' productivity (such as absenteeism, shirking, turnover or training).…”
Section: Introductionmentioning
confidence: 99%